2023
DOI: 10.3390/ijms24054482
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Alterations in Prostate Cancer: Roles in Pathobiology and Racial Disparities

Abstract: Prostate cancer (PCa) affects millions of men worldwide and is a major cause of cancer-related mortality. Race-associated PCa health disparities are also common and are of both social and clinical concern. Most PCa is diagnosed early due to PSA-based screening, but it fails to discern between indolent and aggressive PCa. Androgen or androgen receptor-targeted therapies are standard care of treatment for locally advanced and metastatic disease, but therapy resistance is common. Mitochondria, the powerhouse of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 176 publications
0
6
0
Order By: Relevance
“…This succinate buildup ultimately leads to an epigenetic alteration in carcinomas [ 57 ]. Studies have confirmed the role of succinate in cellular transformation and cancer at both the biochemical and genomic levels [ 66 , 76 ].…”
Section: Succinate-ubiquinone Oxidoreductase (Succinate Dehydrogenase...mentioning
confidence: 99%
“…This succinate buildup ultimately leads to an epigenetic alteration in carcinomas [ 57 ]. Studies have confirmed the role of succinate in cellular transformation and cancer at both the biochemical and genomic levels [ 66 , 76 ].…”
Section: Succinate-ubiquinone Oxidoreductase (Succinate Dehydrogenase...mentioning
confidence: 99%
“…Present at the facade of eliciting chemo-resistance, mitochondria regulate molecular interplay at places of cellular stress and facilitate cell survival. Perturbed mitochondrial functions are commonly observed in cancer, often leading to altered nuclear gene expression via retrograde signalling and promotion of tumour endorsing stromal re-modelling [ 51 ]. Evasion of apoptosis and metabolic re-wiring are endorsed by the mitochondrial components invoking chemo-resistance and metastasis of cancers.…”
Section: Metabolic Switch and Metastatic Impact Of Ages-ragementioning
confidence: 99%
“…Metabolic interaction between tumor cells and the stromal cells varies in different cancers, giving rise to differences in their aggressive nature. Based on the analysis of glycolytic status of tumours, by evaluating the immunohistochemical expression of GLUT-1 and carbonic anhydrase IX (CAIX) in tissue microarray sections from 740 patients with breast cancer, Choi and colleagues [50] classified the molecular subtypes of breast cancer into the following metabolic strata: Warburg type: tumor-glycolysis type, stroma-nonglycolysis type. (1) Reverse Warburg type: tumor-nonglycolysis type, stroma-glycolysis type.…”
Section: Metabolic Insurgence and Cancer Malignancementioning
confidence: 99%
“…Multiple subcellular compartments, particularly mitochondria, experience global lysine hyper-succinylation as a result of succinate buildup brought on by SDH depletion leading to an epigenetic change in carcinomas [32]. Studies have validated the role of succinate in cellular transformation and cancer at both the biochemical and genomic levels [33,34].…”
Section: Epigenetic Alterationmentioning
confidence: 99%